Effect of supplemental rumen-protected lysine, methionine or both added to diet of lactating dairy cows on milk fatty acids profile - Ludmila Křížová (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2010)
The objective of this study was to determine the effect of supplemental lysine (Lys), methionine (Met) or both added to diet of dairy cows in the form of rumen-protected (RP) tablets on changes in milk fatty acids (FA) profile. The trial was carried out on four lactating Holstein cows in the form of Latin square design and was divided into 4 periods of 14 d (10-d preliminary period and a 4-d experimental period). The four treatments were as follows: C – control without amino acids (AA) supplementation, L – supplement of RP Lys, M – supplement of RP Met and ML – supplement of RP Met and Lys. Cows were fed on a diet based on maize silage, lucerne hay and supplemental mixture. Milk yield in ML (34.18 kg/d) was higher than in L or M (32.46 kg and 32.13 kg, respectively, P < 0.05) and tended to be higher than in C (33.33 kg/d, P > 0.05). Protein yield in ML (1054 g / d) was higher than that found in C, L or M (990, 998 or 968 g / d, respectively, P < 0.05). Milk fat content and yield in C and ML was higher in comparison to L and M (P < 0.05). Content of short-chain FA (C 4:0–C 12:0) was not affected by the treatment except of L that was lower than in C (P < 0.05). Content of medium-chain FA in M was lower compared to C, L or ML (P < 0.05). The content of long-chain FA in M was significantly higher than in other groups (P < 0.05). The total content of SFA in M was lower than in C or ML (P < 0.05) and tended to be lower than in L. Contents of UFA, MUFA and PUFA in M were higher than in C and ML (P < 0.05).